2018
DOI: 10.1177/0192513x18792682
|View full text |Cite
|
Sign up to set email alerts
|

The Trouble With Fathers: The Impact of Time and Gendered-Thinking on Working Relationships Between Fathers and Social Workers in Child Protection Practice in England

Abstract: The lives of families entering the child protection arena may be shaped by a range of troubles, including material deprivation, physical and mental health problems, substance misuse or domestic abuse. Despite the interest in whole family approaches, the issue of how professionals fail to work effectively with fathers is longstanding and resistant to change. This paper illustrates challenges in building working relationships with men, including the challenge of avoiding binary thinking in the assessment of fath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…With such a limited sample of men it is not possible to comment in any depth about father engagement suffice to say that all three had completed the intervention and were positive about their involvement. It is worth noting however, that VIG was able to actively engage fathers; something that is widely accepted as challenging (Philip et al, 2018). Such challenges have included a tendency toward rigid, polarized thinking where workers see fathers as either a risk or resource to their children (Scourfield, 2003), tensions around the timing of involving fathers and need for gender sensitivity (Philip et al, 2018), and father avoidance of contact with child welfare services (Maxwell et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…With such a limited sample of men it is not possible to comment in any depth about father engagement suffice to say that all three had completed the intervention and were positive about their involvement. It is worth noting however, that VIG was able to actively engage fathers; something that is widely accepted as challenging (Philip et al, 2018). Such challenges have included a tendency toward rigid, polarized thinking where workers see fathers as either a risk or resource to their children (Scourfield, 2003), tensions around the timing of involving fathers and need for gender sensitivity (Philip et al, 2018), and father avoidance of contact with child welfare services (Maxwell et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Featherstone's (2009) research on father's involvement in social care, found that services constructed fathers as: 'either absent or disinterested' (161). This binary understanding from professional, can have profound consequences for men, women and children (Phillip at al., 2019). Similarly, Hammaŕen et al, (2014) reported that social work interventions for men in Sweden were inclined to draw on 'traditional 'images of gender that were influenced by a compensatory approach in which men were treated as a problem and a risk in society.…”
Section: Barriers To Fatherhood and Seeking Supportmentioning
confidence: 99%
“…There is consensus that fathers have the potential to play a vital role in family life. However, there are concerns about the absence of fathers in families, with children growing up without fathers (ONS, 2005; Phillip et al., 2019; Pickard, 1998; Scottish Government, 2017b). There were 141,000 lone parents with dependent children living in Scotland in 2015, and the majority were female (91%) (Taulbut et al., 2016).…”
Section: Environmental Contextmentioning
confidence: 99%
See 2 more Smart Citations